LA MIGRACIÓN Y SU INFLUENCIA EN LOS VALORES SOCIOCULTURALES DE LA COMUNIDAD DE CAÑICAPAC PERTENECIENTE A LA PARROQUIA DE SAN PABLO DE TENTA, CANTÓN SARAGURO Y LA INTERVENCIÓN DEL TRABAJO SOCIAL. - ORDÓÑEZ GONZÁLEZ, YESSENIA ANABEL (2019)
This research work called, "migration and its influence on the sociocultural values of the community of Cañicapac belonging to the San Pablo de Tenta parish, Saraguro canton and the intervention of the Social Worker", highlights the findings and results, obtained in the field research, in compliance with the specific objectives, which allowed to theoretically base the analysis categories in relation to the object of study, determine the causes and consequences of migration in the socio-cultural values of the community, to prepare a proposal for social intervention whose purpose is to strengthen sociocultural values, since the community is in a process of acculturation. The results obtained in the investigation, show that the main causes that motivate to migrate are the few job opportunities, deterioration in the agricultural system and the economic factor, whose migration triggers social and cultural problems such as family disintegration losing love filiate within the same, abandonment of studies, early pregnancies, drug use and culturally a loss of identity, producing a community acculturation both for those who have migrated, as for those who remain in it. Regarding the loss of identity due to migration, it is mentioned that “migratory flows in indigenous spaces have altered the patterns of cultural reproduction and identity. Causing a sociocultural change in terms of techniques, languages, science, customs, values, traditions and even values and behavior models that are socially transmitted and therefore assimilated, such elements distinguish them from a social group of another.” (Montiel, 2000). The methodology used in the research was based on the application of the scientific method, supported by its auxiliary methods such as inductive - deductive, analytical - synthetic, which allowed direct contact with the inhabitants of the community, through qualitative and quantitative instruments, observation sheet, focus groups and survey, which made it clear that 5 migration influences the socio-cultural values of the community. The total population that was considered through intentional probabilistic sampling was 11 inhabitants in terms of migration, that is, the people who have migrated and returned to the community were taken into account. Against this background, it was considered pertinent to prepare a proposal for social intervention, aimed at strengthening the socio-cultural values of the community, which includes activities and strategies that allow awareness about the importance of preserving and maintaining the socio-cultural values that identify it from others communities.